Paraganglioma treatment with subtotal petrosectomy. Case report - Oliveira, Filipa (2012)
Paragangliomas are rare tumors, particularly in head and neck region. They arise from cells of the autonomic nervous system and are more frequently found in the carotid body, jugular body, glossopharyngeal nerve and vagus nerve. The identification of this neoplasm in the middle ear is based on the clinical manifestations and complementary exams (audiogram, tympanogram, computed tomography and magnetic resonance). The purpose of this case report is to demonstrate that subtotal petrosectomy is a valuable surgical technique for the treatment of glomus tumors of the temporal bone. A 45-year old woman was referred to our hospital for the surgical treatment of a jugulotympanic paraganglioma on the  left ear. The operation included a subtotal petrosectomy, and the complete removal of the tumor was achieved. Subtotal petrosectomy can be performed as an isolated surgical procedure, but most commonly the technique is used as the first surgical step of different approaches for the lateral skull base. Subtotal petrosectomy includes: 1) the emptying of the temporal bone content with preservation of the profound cortical bone and of the labyrinth; 2) the permanent closure of the external auditory canal; 3) the closure of the tympanic pharyngeal orifice of the Eustachian tube; and 4) the obliteration of the cavity with autologous abdominal fat. In the case reported, the patient was discharged at the ninth day after surgery. As surgical consequence, inherent to the technique, the patient had definitive conductive hearing loss. Follow-up was performed annually with magnetic resonance. The therapeutic options for the paragangliomas of the temporal bone include surveillance without therapy, radiotherapy and surgery. The only curative solution is the surgery. In our patient we have opted for the surgical treatment which included the subtotal petrosectomy. One year after surgery, the patient is healed, having returned to her normal activity.